(untitled) (Dermatology Reports, 2023)
Dear Editors, Lichen sclerosus (LS) is a chronic inflammatory disorder affecting mostly – but not exclusively – the genital area. Oldfashioned pseudonyms include balanitis xerotica obliterans and kraurosis vulvae. LS is typically characterized by the presence of hypopigmented atrophic plaques, often accompanied by itching and/or pain...